RELATIONSHIP OF HEALTH CARE QUALITY WITH INTEREST IN PATIENT RE-VISITS AT CANGKRINGAN SLEMAN HEALTH CENTER - Kunik Afifah (Jurnal EduHealth, 2020)
Good quality service will provide satisfaction to customers who eventually customers will take advantage of and recommend the health service to those around them. So that it affects the decision making of repurchases that will later affect consumers about the services provided. Good and quality service will increase the number of visits which will ultimately increase the amount of puskesmas revenue. This study aims to find out the relationship of health care quality with the interest of patient re-visits at Cangkringan Sleman Health Center. This study uses quantitative design with cross sectional research design by means of data collection using questionnaires. The number of samples used in this study as many as 75 respondents with the sampling technique used is accidental sampling. Statistical analysis uses the Contingency Coefficient test with a confidence level of 95% (α=0.05). This study shows that there is a relationship between the quality of health services and the interest in patient re-visits at Sleman Cangkringan Health Center with a value of p = 0.031, r = 0.241. There is a significant relationship between the quality of health services and the interest in re-visits, namely the more patients who visit, the better the quality of Sleman Cangkringan Health Center services.